Microplásticos, suas interações com organismos bentônicos e distribuição nas praias da Ilha da Trindade (Brasil) - PINHEIRO, Lara Mesquita (2017)
The intense pollution on marine and coastal environments have important aspects such as the production and inappropriate disposal of plastic items. These widely used polymers usually accumulate and degrade on those environments forming particles smaller than 5mm called microplastics. These particles present many risks to both coastal environment and biota such as ingestion, blockage of digestive and/or respiratory pathways and toxicological effects caused either by the polymer or by associated pollutants. This work had two objectives corresponding to two chapters of this document: (1) to perform a literature review about microplastic interaction with the coastal environment, focusing on the benthic compartment; (2) to characterize microplastic pollution on sandy beaches of Trindade island, on Espírito Santo state. In the first chapter, 52 articles were analysed, adressing seven animal phyla. This number of works on this issue is relatively small, and mainly laboratorial. It was found that the effects of microplastic ingestion are being reported since the beginning of this century. In general, it was shown that factors such as microplastic characteristics, laboratory methodologies, microplastic concentration and distribution on the sediment are determinant on this type of work. Therefore, there is lack of methodology standardization for microplastic analysis in sediment, as well as a more relevant ecological approach that involves both field and laboratory experiments. In the second chapter, microplastics were isolated from sediment samples from Trindade island using a density separation method. It was found that this island, despite its remote location, is widely contaminated with microplastics smaller than 1mm. Microplastics were found in the shape of fragments and fibres, with densities of up to 311 fragments or 333 fibres per m2. Microplastic deposition dynamics in sediment is strongly related to current, wind and tidal systems. However, factors affecting this dynamic for microplastics smaller than 1mm remains unclear. Considering that Trindade island has high ecological importance, these results show that future studies are extremely necessary to determine the risks to which the island’s coastal ecosystem is submitted to.